A Critical Study of Farhat Parveen's Fiction - Azeem, Sarwar (sourcecoder, 2024)
Farhat Parveen is the best fiction writer of Urdu. His legendary collections include "Munjmid, Restauran ki khirki se, Bezum Shisha Gran, Kanch ki chatan, Sandal ka jungal". Farhat Parveen has been a member of various welfare and literary organizations. She is the speak up daughter of Ahmad Nadeem Qasmi. She had close relations with most of the famous authors of literature, including Amjad Islam Amjad, Attaul Haque Qasmi, Mushtaq Ahmad Yousufi and Khawaja Muhammad Zakaria. Farhat Parveen stayed in different countries. Her first fiction collection titled "Munjmid" was published in 1997. She wrote fiction on women's rights, feminist sentiments and women's issues. In her fictions, European and Oriental women are depicted. Furthermore, she satirizes the class system in the society. Rare ideas, styles of thinking, variety of themes, unique style of writing and modern style of thinking are found in her fictions. She has presented human psychology in a deeply conscious and logical manner. There is continuity and attraction in the plot of fiction. She has presented all the facts of life very well.